Domain specific cognitive impairment in Parkinson's patients with mild cognitive impairment. (May 2020) - Chaudhary, Shefali; Kumaran, S Senthil; Kaloiya, G.S.; Goyal, Vinay; Sagar, Rajesh; Kalaivani, M.; Jaganathan, N.R.; Mehta, Nalin; Srivastava, Achal
Highlights: PD cognitive profile is widespread and heterogeneous. Memory and executive/Visuospatial functions are impaired in PD-MCI in comparison with HC/PD-NC. PD clinical variables significantly affect cognitive performance. The most prominent clinical score affecting cognition is the 'motor score (UPDRS-III)'. Visuospatial executive function and memory cognitive domains are promising in defining PD-MCI stage. Abstract: Mild cognitive impairment (MCI) affects nearly 20–50% patients with Parkinson's disease (PD). It may be the prodromal stage of dementia and impacts quality of life of the patient and caregiver. Characterizing PD cognition at the stage of MCI may help in understanding of cognitive pathophysiology. This study assessed and compared cognition in patients with PD and mild cognitive impairment (PD-MCI, n = 32, age = 61.09 ± 5.97 years), PD patients with normal cognition (PD-NC, n = 32, age = 58.81 ± 6.15 years) and healthy controls (HC, n = 38, age = 57.39 ± 7.14 years). Montreal Cognitive Assessment Test (MoCA) was used for categorization of subjects. Cognitive assessment of five domains: executive function, attention, visuospatial function, memory and language (using two tests in each domain) were performed. The effect of PD clinical scores on cognition and cognitive domain specificity in diagnosing PD-MCI were assessed by correlation and receiver operating curve (ROC) analyses, respectively. All the analyses followed removal of potential confounds (age, education and clinical scores). Attention, memory, executive and visuospatial functions were impaired in PD-MCI on comparison with HC and PD-NC groups. Performance in digit span forward and trail making tests for attention and memory (immediate recall) were comparable in both the PD groups. Both the PD groups revealed impairment in attention, memory and language with respect to HC, suggesting the fronto-striatal and posterior cortical syndrome in PD. Highly significant Visual-N-back correlation with UPDRS-III may implicate the shared motor-visuospatial neural pathways. Visual-N-back/PGI delayed recall domains are promising in characterizing PD-MCI stage.